Parainfluenza virus infections in patients with hematological malignancies or stem cell transplantation: analysis of clinical characteristics, nosocomial transmission and viral shedding - Tabatabai, Julia; Schnitzler, Paul; Prifert, Christiane; Schiller, Martin; Weißbrich, Benedikt; Lilienfeld-Toal, Marie von; Teschner, Daniel; Jordan, Karin; Müller-Tidow, Carsten; Egerer, Gerlinde; Giesen, Nicola (PLOS ONE, 2022)
To assess morbidity and mortality of parainfluenza virus (PIV) infections in immunocompromised patients, we analysed PIV infections in a hematology and stem cell transplantation (SCT) unit over the course of three years. Isolated PIV strains were characterized by sequence analysis and nosocomial transmission was assessed including phylogenetic analysis of viral strains. 109 cases of PIV infection were identified, 75 in the setting of SCT. PIV type 3 (n = 68) was the most frequent subtype. PIV lower respiratory tract infection (LRTI) was observed in 47 patients (43%) with a mortality of 19%. Severe leukopenia, prior steroid therapy and presence of co-infections were significant risk factors for development of PIV-LRTI in multivariate analysis. Prolonged viral shedding was frequently observed with a median duration of 14 days and up to 79 days, especially in patients after allogeneic SCT and with LRTI. Nosocomial transmission occurred in 47 patients. Phylogenetic analysis of isolated PIV strains and combination with clinical data enabled the identification of seven separate clusters of nosocomial transmission. In conclusion, we observed significant morbidity and mortality of PIV infection in hematology and transplant patients. The clinical impact of co-infections, the possibility of long-term viral shedding and frequent nosocomial transmission should be taken into account when designing infection control strategies.